Historiografi Mahar Hafalan Alquran Dalam Pernikahan - Ibnu Irawan; Jayusman Jayusman; Agus Hermanto (UIN SYEKH ALI HASAN AHMAD ADDARY PADANGSIDIMPUAN, 2019)
The Messenger of Allah (PBUH) was easy to give his marriage dowry in keeping with the Qur'an.The history of The Islamic Dowry preserved the Qur'an from its beginning to the present has witnessed an interesting development of the study.The dowry of the qur'an's preservation of the marriage practiced by people today is driven by the lack of conformity with the history that occurred at the time.From previous backgrounds, the author is more studying through a historical approach to discovering developments that have taken place since the beginning of the Qur'an.'The results of this study show that the payment of a dowry from the Qur'an is currently witnessing the development of the meaning of dowry on the one hand, which is actually happening and the bottom now in society today is not limited to concern with the elements of rightsonly women, but increased attention to other aspects as well as the circumstances of the interest of the rightsTherefore, islamic law in its historical review is valid for all time and place. Keywords: RightsWomen: Marriage Dowry: History: Memorizing the Qur'an.